Evolution is a double‐edged sword, not a silver bullet, to confront global change. Issue 1 (4th June 2020) - Diamond, Sarah E.; Martin, Ryan A.
Abstract: Although there is considerable optimism surrounding adaptive evolutionary responses to global change, relatively little attention has been paid to maladaptation in this context. In this review, we consider how global change might lead populations to become maladapted. We further consider how populations can evolve to new optima, fail to evolve and therefore remain maladapted, or become further maladapted through trait‐driven or eco–evo‐driven mechanisms after being displaced from their fitness optima. Our goal is to stimulate thinking about evolution as a "double‐edged sword" that comprises both adaptive and maladaptive responses, rather than as a "silver bullet" or a purely adaptive mechanism to combat global change. We conclude by discussing how a better appreciation of environmentally driven maladaptation and maladaptive responses might improve our current understanding of population responses to global change and our ability to forecast future responses. Abstract : In this review and synthesis, we explore how global change can cause populations to become maladapted and how populations, in turn, exhibit adaptive or maladaptive responses to global change. We use the metaphor of a "double‐edged sword" to explore these evolutionary responses to global change. As the double‐edged sword has both beneficial and detrimental effects, evolutionary responses to global change likewise involve both adaptive and maladaptive responses.